"How Am I Not Myself?" Despair in Sickness Unto Death as Misguided Attempts Toward Self-Actualization. (March 2016) - Oaks, Cody L.
This article is an attempt at a creative exegesis of Kierkegaard's diagnosis of despair in Sickness Unto Death, that is, the overextension of the self into one side of the polarities of personality that should be a synthesis: infinity, finitude, and possibility–necessity are explored. For each instance of despair, I provide concrete examples of how this type of despair manifests itself in everyday life and in our current cultural context. Finally, the role of faith, as a means to curb despair and allow the self to actualize, is discussed over against the attempt to assert the self as an act of defiance.